2011
DOI: 10.1002/app.35553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new soluble multisite phase transfer catalysts and their catalysis in free radical polymerization of methyl methacrylate aided by ultrasound—A kinetic study

Abstract: Four different soluble phase transfer catalysts (PTCs) containing single, di, tri, and tetra active sites have been prepared and proved by FT‐IR, 1H NMR, 13C NMR, mass, elemental analysis, and conductivity measurement. The presence of the number of active sites in each catalyst was also been confirmed by determining their rate of polymerization of methyl methacrylate (MMA) using potassium peroxydisulfate (PDS) as a water soluble initiator in biphase medium. The comparative study reveals that the Rp of MMA dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The enhancement in the rate of phase-transfer catalyzed polymerization under ultrasound condition is attributed to the aforementioned reason. The combined approach of PTC and ultrasound is one of best techniques to enhance the reaction rate [60][61][62][63][64][65].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The enhancement in the rate of phase-transfer catalyzed polymerization under ultrasound condition is attributed to the aforementioned reason. The combined approach of PTC and ultrasound is one of best techniques to enhance the reaction rate [60][61][62][63][64][65].…”
Section: Resultsmentioning
confidence: 99%
“…2). The reason was mainly attributed to the mechanical and chemical effect of ultrasound which can enhance the mixing of two phase effectively making like homogenous phase and helps the formation and transfer of more radical along with phase transfer catalytic polymerization process [60][61][62][63][64][65]. The polymerization of acrylonitrile with different PTC was reported [25,34,35,42] in the absence of ultrasound condition.…”
Section: Variation Of Time On the R Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [11,12] also reported a kinetic study of dichlorocyclopropanation of 4-vinylcyclohexne and etherification of 4,4 -bis(chloromethyl)-1,1 -biphenyl and 1-butanol catalyzed by using new soluble MPTC containing two active sites and showed that MPTC exhibits more reactivity than single-site PTC. In our laboratory too, several multi-site phase transfer catalysts are reported for alkylation [13][14][15][16], dichlorocarbene addition [17,18], asymmetric synthesis [19][20][21][22], decarboxylation [23], functionalization of multi-walled carbon nano tubes [24,25] and polymerization [26] reactions.…”
Section: Introductionmentioning
confidence: 99%